SEBARAN SUKUN DAN PERSEPSI MASYARAKAT TERHADAP SUKUN (Artocarpus communis Forst) PADA DAERAH TANGKAPAN AIR DANAU TOBA DI NAGORI PURBA SARIBU KECAMATAN HARANGGAOL HORISON KABUPATEN SIMALUNGUN - Jordy M Manurung; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2015)
Forests and land in the catchment area of Lake Toba, showed a decrease for quality and quantity of the land. This study aims to determinethe public perception of breadfruit (Artocarpus communis Forst). Research carried out in the catchment area of Lake Toba, Simalungun. Analysing public perception using a questionnaire. Data from the questionnaire were analyzed by descriptive quantitative. Perceptionis influencedby factors of age, education, livelihood and long lived. Research shows that there is a breadfruit distribution point in Haranggaol. Public perception of the breadfruit (Artocarpus communis Forst) is good. Where 58.41% of the people know and understand the benefits of breadfruit.Keywords: Breadfruit (Artocarpus communis Forst), Distribution of Breadfruit, Community Perception, Forest, Catchment Area